Projektno financiranje železniške infrastrukture - Romih, Dejan (Naše gospodarstvo, 2007)
In this paper we present a 'Build, Operate, Transfer' (BOT) model of financing railway infrastructure development in the Republic of Slovenia. It is characteristic of this form of project financing that the host country or a local community grants a private project company or consortium a concession to build and manage the public infrastructure. By signing the concession contract, the concessionaire binds himself/herself to transfer all the property rights from the project back to the grantor at the end of the concession period without additional transaction costs at the end of the concession period.
Keywords: Slovenia; Slovenija; železniško gospodarstvo; železnice; železniške proge; gradnja; financiranje; koncesije; javni sektor; public sector; privatni sektor; partnerstvo